STRATEGI MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN KUALITAS LEMBAGA PENDIDIKAN - Zulfahmi Mar’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze Islamic education management strategies in improving the quality of Islamic educational institutions. The focus of the study is directed at the role of planning, resource management, program implementation, and continuous evaluation as the main components of quality improvement. This research employs a qualitative approach using a library research method. Data were collected from scholarly books, national and international journal articles, and academic documents relevant to Islamic education management and institutional quality. Data analysis was conducted through systematic and in-depth content analysis. The findings indicate that the implementation of integrated and quality-oriented Islamic education management strategies significantly contributes to improving teachers’ performance, fostering a positive organizational culture, and stengthening public trust in Islamic educational institutions. Therefore, Islamic education management strategies play a crucial role in realizing high-quality, competitive, and sustainable Islamic educational institutions.